Money and Credit : Theory and Applications - Wang, Liang; Liu, Lucy Qian.; Wright, Randall (Washington, D.C. : International Monetary Fund, 2017)
We develop a theory of money and credit as competing payment instruments, then put it to work in applications. Buyers can use cash or credit, with the former (latter) subject to the inflation tax (transaction costs). Frictions that make the choice of payment method interesting also imply equilibrium price dispersion. We deliver closed-form solutions for money demand. We then show the model can simultaneously account for the price-change facts, cash-credit shares in micro payment data, and money-interest correlations in macro data. We analyze the effects of inflation on welfare, price dispersion and markups. We also describe nonstationary equilibria as self-fulfilling prophecies, which is standard, except here it entails dynamics in the price distribution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet